Harald Wezler som erindringsforsker: En viderefører af Halbwachs-Assmann-traditionen? - Jensen, Bernard Eric (Tidsskriftet Antropologi, 2005)
Bernard Eric Jensen: Harald Welzer’s Approach to Memory Research An analysis of the approach to memory research found in the writings of Harald Welzer is presented. At the present time, Welzer is head of the Centre for Interdisciplinary Memory Research at Kulturwissenschaftliches Institut in Essen, Germany. He has contributed both empirical surveys and theoretical analyses to memory research during the last decade. At a first glance, Welzer’s approach appears to belong neatly within the tradition of memory research that was originally founded by the French sociologist Maurice Halbwachs, and which Aleida and Jan Assmann have been seeking to revive and develop since the 1980’s by introducing concepts such as “communicative and cultural memory” as well as “storage memory” (Speicher-Gedächtnis) and “use memory” (Funktions-Gedächtnis). On closer inspection, however, it transpires that Welzer’s approach cannot be characterised as a mere refinement of the approach taken by the Assmanns. This is partly because Welzer is attempting to develop an interdisciplinary approach, focused on the intricate relationships between biological, psychological and social factors in ongoing memory work. Apart from focussing of the work of Welzer, this article also seeks to highlight the state of “terminological anarchy” that characterises memory research at the present time, making it next to impossible to make direct comparisons between different theoretical approaches. This state of anarchy becomes transparent as soon as one begins to scrutinize the meanings of those adjectives, which nowadays are fixed to the term memory – for instance, “communicative”, “cultural”, “historical” and/or “social” memory.